Chapter La ricezione di Dante presso i serbi (1991-2021) - Lazarevic Di Giacomo, Persida (Biblioteca di Studi di Filologia Moderna, 2022)
This paper examines the reception of Dante among Serbs in the period between 1991 to 2021. It focuses on the complex state of Serbian Danteology in the crucial historical period in which Yugoslavia was beginning to crumble and Serbia was subjected to sanctions and isolated from the world, and which also includes the NATO bombings. The examination concludes in 2021, which coincides with the 700th anniversary of Dante's death. The paper focuses primarily on translations of Dante's works (mostly the Divine Comedy) by two Serbian translators, Dragan Mraović and later Kolja Mićević, but also on republished translations such as those by Dragiša Stanojević and Mihovil Kombol. The Serbian studies and theatrical performances of Dante's work are also considered.